Penatalaksanaan Fisioterapi pada Kasus Sprain Ankle Dekstra dengan Modalitas Ultrasound Therapy dan Terapi Latihan di RSUD Bandung Kiwari - Andhira Roudlotul Jannah; Abdul Qudus (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
ankle sprain is an injury that occurs to the lateral complex ligaments due to excessive stretching accompanied by inversion and plantar flexion which occurs suddenly when the foot does not rest perfectly on an uneven floor/ground surface. To determine the implementation of Physiotherapy in reducing pain, increasing muscle strength, increasing the Scope of Joint Movement and preventing re-injury in cases of right ankle sprains using Ultrasound therapy and Exercise Therapy modalities. After undergoing therapy 6 times, the results using VAS showed a decrease in pain in silent pain, obtained a value of 2 at T1 & T2, a value of 1 at T3 - T5 and a value of 0 at T6. Pressure pain was obtained with a value of 3 at T1 - T3, a value of 2 at T4 and a value of 1 at T5 & T6. Movement pain was obtained with a value of 6 on T1 & T2, a value of 5 on T3 then a value of 4 on T4 4. On T5 & T6, the pain value was reduced to 3. There was an increase in the range of motion of the joint in the right Ankle joint in the sagittal plane, the results of T1 & T2 were obtained (S = 10ᴼ – 00ᴼ – 30ᴼ) T3 & T4 (S = 15ᴼ - 00ᴼ - 35ᴼ) and T5 & T6 there is an increase in the range of motion of the joints in the sagittal plane, namely (S = 20ᴼ - 00ᴼ - 35ᴼ ). In the Value Rotation field at T1 (R = 25ᴼ - 00ᴼ - 10ᴼ) then at T2 (R = 30ᴼ - 00ᴼ - 10ᴼ) at T3 (R = 30ᴼ - 00ᴼ - 15ᴼ) The value of T4 - T6 has an increase in value to (R = 30ᴼ - 00ᴼ - 20ᴼ). There was an increase in muscle strength by using MMT in the dorsiflexion plane of motion, a value of 4+ was obtained at T1-T3, a value of 5 at T4 - T6. Plantar flexion obtained a value of 4- at T1 & T2, a value of 4 at T3 & T4 and a value of 4+ at T5 and at T6 a value of 5. Inversion obtained a value of 4 at T1 & T2, a value of 4+ at T3 – T5 and a value of 5 at T6 . Eversion was obtained with a value of 4 at T1 & T2, a value of 4+ at T3 and an increase in value to 5 at T4 - T6. Ultrasound can reduce pain and reduce muscle tension, Theraband Exercise can increase the range of motion of joints, and Calf raises can increase muscle strength.